SWOT Based Principal Strategy (Strengths, Weaknesses, Opportunities, And Threats) in Improving the Quality of Muara Badak Integrated Islamic Elementary School - Restiawati, Yanti; Komariyah, Laili; Dwiyono, Yudo; Masruhim, Amir; Hidayanto, Dwi Nugroho; Haryaka, Usfandi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The use of SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is a crucial tool in identifying and understanding the competitive position of a school. This research aims to describe the principal's strategy based on SWOT analysis in improving the quality of Muara Badak Integrated Islamic Elementary School. This research used a qualitative approach with a case study method conducted through interviews, observation, and documentation. The research results using SWOT analysis show that SDIT (Sekolah Dasar Islam Terpadu, Integrated Islamic Elementary School) Muara Badak improves the quality of education by 1) utilizing internal strengths systematically through the principal's leadership, which involves teachers, committees, and parents in policymaking; 2) the foundation provides financial support and resources without operational intervention, while the committee and parents actively contribute to school funding and activities; 3) the principal addresses administrative weaknesses by focusing on learning outcomes using clear guidance books and postponing the use of risky technology; 4) the school also leverages its position as the only integrated Islamic school in the region by strengthening branding through social media and teachers' role modeling of Islamic values. The threat of a less strategic location is overcome by providing school shuttle services, increasing parents' trust and the number of registrants; 5) routine evaluations and strengthening teachers' spirituality through reciting activities and close collaboration between the foundation, committees, and parents are key to the success of continuous quality improvement. Research recommendations include conducting comparative studies to identify best practices by comparing SDIT Muara Badak with other schools and developing an implementation model for a SWOT-based quality improvement strategy that can be widely applied by considering each school's context